Fiscal Policy Analysis on Economic Growth in Indonesia Period 2010-2023 (VECM Approach) - Dara Ditha, Meylani; Muhammad Iqbal; Zulaikah (International Journal of Economics (IJEC), 2025)
This study analyzes the effect of fiscal policy on Indonesia's economic growth in the period 2010-2023 using the Vector Error Correction Model (VECM) approach. The results show that capital expenditure has the most significant effect on economic growth in the long term, with the highest fiscal multiplier compared to other instruments. Social spending and subsidies also contribute positively to growth, especially in maintaining people's purchasing power during periods of crisis, such as the COVID-19 pandemic. In terms of revenue, value added tax and income tax show a positive correlation with economic growth, although their effectiveness depends on the tax structure and taxpayer compliance. This study also finds that a well-managed budget deficit can act as a development instrument that encourages productive investment and increases economic output sustainably. In addition, the analysis of the impulse response function (IRF) and forecast error variance decomposition (FEVD) shows that government spending instruments have a greater impact than tax instruments on the dynamics of Indonesia's economic growth. The policy implications of this study emphasize the need to optimize capital spending, reform social spending, increase the tax ratio through comprehensive tax reform, and manage the deficit wisely to maintain fiscal stability. In conclusion, effective and targeted fiscal policy can be a major catalyst in accelerating economic growth and supporting the structural transformation of the Indonesian economy towards a more inclusive and sustainable direction.